Environmental Court and Principle of Good Environmental Governance in Enforcing Environmental Law - Aju Putrijanti; Irma Cahyaningtyas (Varia Justicia, 2023)
Environment dispute settlement carried out by general and administrative court, depends on the object of disputes. Government has to based on principle of good environmental governance when issue the permit and policies. The issues are the urgency to build environmental court and implementation of principle of good environmental governance. Method use is juridical normative, primary data used are regulations, secondary data are expert opinions, articles. Data analysis qualitatively and describe in descriptive analysis. Environmental court will be under Administrative Court as special court, which comprises of private, penal and administrative chamber. Implementation of principle of good environmental governance through issue permit, policies and supported by strengthen law enforcement. Regulations as based of law to build environmental court has to be synchronized with relevant regulations in order to enforce the environmental law enforcement and gives environmental justice. Novelty in this research is build environmental court to strengthen environmental law enforcement.